Efektivitas Penggunaan Media Pembelajaran Berbasis Augmented Reality dan Metode Pembelajaran Active Learning Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI dalam Kurikulum Merdeka, dengan Motivasi Belajar Sebagai Variabel Moderasi - Siti Fauziyah; Ida lutfiyatul Jamilah; Ririn Inayatul Mahfudloh (Pascasarjana Universitas Qomaruddin, 2024)
The phenomenon or research problem is the use of augmented reality (AR)-based learning media and active learning methods in the context of Islamic Religious Education (PAI) lessons at SMAN 1 Dukun. This issue arises from the need to evaluate the effectiveness of innovative learning methods and emerging technologies, as well as their relevance in improving student learning outcomes. The purpose of the research is to provide new insights on how to enhance PAI learning and enrich the Merdeka curriculum with relevant technology and teaching methods. This research uses quantitative methods and descriptive hypotheses. The researchers used data analysis techniques in the form of PLS SEM with the assistance of SmartPLS 4.0 to address the objectives of the study. The research sample consists of students from SMAN 1 Dukun who are studying the subject of PAI. We use random sampling, a method that selects samples randomly without distinguishing between the strata or levels of the students from SMAN 1 Dukun Gresik. This research instrument consists of a closed questionnaire filled out online using Google Forms. The questionnaire takes the form of a Likert scale. We conducted technical data analysis using moderation regression tests, t-tests, and R-Square tests. The study shows that augmented reality (AR)-based learning media and active learning methods have a big direct impact on how well students at SMAN 1 Dukun learn. The T-statistic value is 3.673, which is higher than 1.96 (for 5% significance), and the path coefficient value is positive (0.553). The correlation value between augmented reality (AR)-based learning media and active learning methods and the learning outcomes of students at SMAN 1 Dukun is 94.3% .